Environmental Sustainability 2014
DOI: 10.1007/978-81-322-2056-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Role of Arbuscular Mycorrhizal Fungi in Sustainable Agriculture

Abstract: Sustainable agriculture plays a vital role in agroecosystems and reduces adverse effects on the environment by utilizing the various natural processes. Optimum soil fertility is an essential goal to be achieved in sustainable agriculture system. The presence of benefi cial microorganisms in the rhizospheric region and their activities are the main focal point which makes dynamic resources available to plants and conserve soil fertility. Majority of the agricultural and horticultural crops are associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 284 publications
(168 reference statements)
1
5
0
Order By: Relevance
“…Apart from daily watering, plants treated with AMF were observed to grow better with a higher number of leaves. This finding is in tandem with the report of Oyetunjiet al 2007;Priyadharsini and Muthukumar, 2015 who reported that mycorrhizal association is capable of ameliorating all forms of stress and aid the formation of better vegetation in plants. However, the loss of leaves by both inoculated and non-inoculated plants could be due to leaf aging and mechanism for water conservation since the higher the number of leaves, the higher the rate of transpiration.…”
Section: Discussionsupporting
confidence: 88%
“…Apart from daily watering, plants treated with AMF were observed to grow better with a higher number of leaves. This finding is in tandem with the report of Oyetunjiet al 2007;Priyadharsini and Muthukumar, 2015 who reported that mycorrhizal association is capable of ameliorating all forms of stress and aid the formation of better vegetation in plants. However, the loss of leaves by both inoculated and non-inoculated plants could be due to leaf aging and mechanism for water conservation since the higher the number of leaves, the higher the rate of transpiration.…”
Section: Discussionsupporting
confidence: 88%
“…Arbuscular mycorrhizal fungi interact at the root-soil interface in a coordinated manner. Their hyphae absorb and translocate water and nutrients from the soil to the plant to increase its growth and development (Dwivedi, 2015;Priyadharsini & Muthukumar, 2015). Wheat is colonized by mycorrhizae, but colonization depends on AMF strains and soil conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Status and potential of mushroom industry in Malaysia. Economic and Technology Management Review, v. 9, p. [103][104][105][106][107][108][109][110][111]2014.…”
Section: Referências [1]mentioning
confidence: 99%